2019
DOI: 10.1080/09712119.2019.1617719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different methionine sources on growth performance, meat yield and blood characteristics in broiler chickens

Abstract: Three graded levels of MHA (methionine hydroxyl analogue) added into the broilers' diets were based on the assumption that the relative bioavailability of MHA sources to DL-methionine (DLM) on a molar basis was 100%, 90% or 80% to meet the requirement of total sulphur amino acids. DLM was used as the reference control group. Live body weight at 21 and 35 days was retarded (p < 0.05) in chicks fed a diet containing 100% equivalent MHA-FA (methionine hydroxyl analogue free acid) across dietary treatments. Chicks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…Except for leg weight results, the results are in agreement with what (Esteve and Khan, 2018) who announced in their study on adding different sources of liquid methionine that carcass yields, as a percentage of live body weight, were not affected by dietary treatments. The results of the carcass traits in this study are inconsistent with what was found by (Kim et al, 2019), they confirmed that there were significant differences between the different nutritional factors in the carcass parts when feeding various sources of liquid methionine to broiler chicks. Some of the results achieved in this study are not consistent with what is found by (Conde et al, 2016), where they emphasized in their study on broiler chicks the sources of methionine had significant (P ≤ 0.05) effects on the liver and heart weight, while methionine levels significantly influenced (P ≤ 0.05) the liver and gizzard weight.…”
Section: Resultscontrasting
confidence: 99%
“…Except for leg weight results, the results are in agreement with what (Esteve and Khan, 2018) who announced in their study on adding different sources of liquid methionine that carcass yields, as a percentage of live body weight, were not affected by dietary treatments. The results of the carcass traits in this study are inconsistent with what was found by (Kim et al, 2019), they confirmed that there were significant differences between the different nutritional factors in the carcass parts when feeding various sources of liquid methionine to broiler chicks. Some of the results achieved in this study are not consistent with what is found by (Conde et al, 2016), where they emphasized in their study on broiler chicks the sources of methionine had significant (P ≤ 0.05) effects on the liver and heart weight, while methionine levels significantly influenced (P ≤ 0.05) the liver and gizzard weight.…”
Section: Resultscontrasting
confidence: 99%
“…Immediately after scanning the broiler carcasses, breast muscles (pectoralis major and minor), drumsticks (muscle), and thighs (muscle) were removed from the carcasses and individually weighed to determine cut yield. Thigh, drumstick, and breast meat yields were expressed as a percentage of the live body weight as described previously [ 27 , 28 , 29 ]. The live body weight is described and published as individual body weight in de Souza et al [ 5 ].…”
Section: Figurementioning
confidence: 99%
“…Information about the relative biological efficacy (RBE) of MHA‐FA compared with dl ‐Met is a relevant factor for cost‐effective purchasing, feed formulation and animal production (Kim et al., 2019 ; Sauer et al., 2008 ). Through the years, there's been considerable research into the potency and usage of these various Met sources, and it has been reported that both Met sources allow for accurate balancing of the dietary SAAs in poultry nutrition.…”
Section: Introductionmentioning
confidence: 99%